ANALISIS PENGARUH KOMPENSASI, JOB INSECURITY, DAN KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION PADA KARYAWAN PT. BATIK AIR INDONESIA DI DIREKTORAT OPERASIONAL - Saputra, Nova Hadi; Soehari, Tjiptogoro Dinarjo (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2019)
Turnover intention at PT. Batik Air Indonesia increased in every years which are affected by compensation, job insecurity and organizational commitment. This study aims to examine and analyze the effect of compensation, job insecurity, and organizational commitment on the turnover intention the operational directorate employees at PT. Batik Air Indonesia. The kind of research used is quantitative research with survey. Polpulation are all of the Employees PT. Batik Air Indonesia, the determining of sample researcher with nonprobability sampling method with use slovin formulation which is use 5% error of the value with the result are 136 respondense. Analysis data is multiple linear regression. The results from this research showed that (1) compensations had a negative and significant effect to turnover intention; (2) job insecurity had a positive but and significant effect to turnover intention; (3) organizational commitment had a negative and significant effect to turnover intention. (4) compensation, job insecurity and organizational commitment simultaneously had a positive significant effect to turnover intention. The conclusion of this research is turnover intention could be reduce by increase the compensation, decrease the job insecurity and organizational commitment